High-performance Building Envelope: an Energy Evaluation of Double-skin Facades Linked into the Earth - (:unkn) unknown (My University, 2017)
ABSTRACT HIGH-PERFORMANCE BUILDING ENVELOPE: AN ENERGY EVALUATION OF DOUBLE-SKIN FACADES LINKED INTO THE EARTH by Payman Sadeghi The University of Wisconsin-Milwaukee, 2017 Under the Supervision of Professor D. Michael Utzinger Good Architecture inclusively addresses all the matters that should and could be considered including but not limited to economic, social, or environmental dimensions. One might perceive ecological architecture in the same way; in reaching high-performance architecture regarding the “good,” wherein the integration of an ecological worldview should be recognized as a fundamental goal. In this domain, energy is surely a crucial concern. This dissertation’s focus is to examine ways to optimize the Load Intensity (LI) of buildings with a Double-Skin Facade (DSF) as an integrated, high-performance building envelope system. A high-performance design rooted in ecological architecture can diminish the built environments’ dependency on exhaustible energies. Instead of these, non-fossil energy sources such as sun, earth, wind and water could be employed to supply built environments’ necessities. It is, thus, critical to assimilate this approach into architectural design from early stages in order to create high-performance buildings that are formed as environmental systems rather than as standalone objects. From social and environmental standpoints, DSFs are presumed as smart, high-performance solutions, which can improve the quality of both indoor and outdoor surroundings. Yet, DSFs’ economic performance is debated. Specifically, a DSFs’ goal to minimize building energy use in different climatic conditions is controversial, presenting it occasionally as not the most economically viable solution. In this dissertation, it is hypothesized that by linking a DSF into the earth, as the second major natural resource, the building’s energy demands would be reduced, and as result its economic performance will be also improved. This hypothesis is examined by designing a system that combines a naturally-ventilated DSF, inspired by the vernacular architectural concept of Persian wind-catchers, with the idea of “geothermal” implementing Earth-Tubes systems, inspired by the concept of Roman hypocausts. To conduct the inquiry, a simulation method is applied that employs both TRNSYS and CANTAM softwares to model and explore energy performance of potential proposed systems.
Keywords: Architectural Design; Double Skin Facade (dsf); Energy Use Intensity; High-performance Buildings; Load Intensity; Sustainability